Palestinian undergraduate learners foreign language classroom anxiety in online environments - Qaddumi, Husam Ahmad; Smith, Matt; Alawneh, Yousef; Shawamreh, Nader; Bakeer, Aida; Itemizeh, Mahmoud (Studies in English Language and Education, 2023)
Despite foreign language classroom anxiety having been studied since the 1980s, there has been little research into this phenomenon in the context of online and blended learning environments. There is a clear need for this study as higher education becomes ever more adaptable, post-pandemic. The portfolio of methods for supporting teaching and learning is widening, with most institutions now offering online and hybrid modules and courses. The purpose of this study was to investigate the levels of anxiety among Palestinian undergraduates learning the English language through online courses. This study also investigated the effects of gender variables (310 males and 1210 females) on foreign language classroom anxiety levels. We surveyed a random sample of 1520 undergraduate students from different universities in Palestine. We used the well-established Foreign Language Classroom Anxiety Scale FLCAS (Horwitz et al., 1986; Horwitz, 2016), which is the most commonly-used measure of anxiety related to language learning. The findings of the study revealed that undergraduate learners experience anxiety when speaking with native speakers. Results indicate no significant differences in the students gender and foreign language classroom anxiety at universities. However, female learners were more anxious in language classrooms where the level of classroom anxiety was high. Finally, we offer tentative solutions for how tutors can support students experiencing foreign language anxiety.